Evaluasi Pelatihan dan Pendampingan Penulisan Artikel Ilmiah bagi Mahasiswa Lintas PTKI di Indonesia - Wahyudin Darmalaksana; Adi Kurnia; Hidayatul Fikra; Fitriani Fitriani (Gunung Djati Conference Series, 2024)
This research aims to evaluate the implementation of training and assistance in writing scientific articles for students across Islamic Religious College throughout Indonesia. This research uses Participatory Action Research combined with the Asset Based Community Development method. The results and discussion of this research show that the implementation of training and mentoring resulted in successful scientific publications for students, even though various obstacles were encountered. First, pre-implementation aspects, such as the lack of motivation for some participants, lack of focus in understanding the writing module, and busy course assignments. Second, aspects of writing practice, such as difficulties in determining research topics, writing research backgrounds, writing problem formulations, writing previous research results, and writing frameworks. Third, post-activity aspects that require the formulation of a scientific publication strategy. This research concludes that the performance of training and assistance in writing scientific articles for students across Islamic Religious College throughout Indonesia with the various obstacles they face is considered quite adequate. This research recommends that administrators of Islamic Religious College prepare plans for effective training and mentoring models as a comprehensive system from upstream to downstream that can ensure the success of scientific publications for students of Islamic Religious College throughout Indonesia.